Pioneering Sustainability: The Development and Policy Framework of Ammonia Fuel Technology in China - Xia, Tian; Ma, Zhihao; Li, Miao (International Journal of Energy Economics and Policy, 2024)
This article investigates the complex dynamics of ammonia as an alternative fuel within the ambit of China’s strategic initiatives aimed at attaining carbon neutrality. Given ammonia’s distinctive characteristics as a fuel, this analysis delves into the nascent development status and the multifaceted challenges confronting this sector within China. Through a comprehensive examination of the plethora of new energy policies promulgated by the Chinese government, this article underscores the initial phase of accelerated growth in the ammonia fuel domain. The imposition of carbon emission restrictions, coupled with the momentum generated by technological innovations, positions green ammonia as an efficacious solution for hydrogen storage and utilization, thereby fostering a symbiotic relationship with the hydrogen energy industry chain. The proactive policy framework adopted by China significantly enhances the pivotal role of ammonia fuel technology, making it one of the principal technological pathways for China to realize its carbon neutrality ambitions in the future.